2016
DOI: 10.1159/000446982
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Use of Fetal Intelligent Navigation Echocardiography (FINE) to Obtain Standard Fetal Echocardiography Views

Abstract: Objective: To evaluate the performance of Fetal Intelligent Navigation Echocardiography (FINE) applied to spatiotemporal image correlation (STIC) volume datasets of the normal fetal heart in generating standard fetal echocardiography views. Methods: In this prospective cohort study of patients with normal fetal hearts (19-30 gestational weeks), one or more STIC volume datasets were obtained of the apical four-chamber view. Each STIC volume successfully obtained was evaluated by STICLoop™ to determine its appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 71 publications
(87 reference statements)
6
64
0
Order By: Relevance
“…The difference in the percentage of satisfactory rating views between the two methods was 1.73% (95% CI, 0.5% -3.33%) with P value of 0.144 which is insignificant. Our results showed a strong agreement with other investigators as Garcia M et al [4], who found that FINE was successful to generate the nine planes in 98% -100% of cases and also Veronese P et al [10] who found that FINE was successful to generate the nine planes in 96% -100% of cases.…”
Section: Discussionsupporting
confidence: 93%
“…The difference in the percentage of satisfactory rating views between the two methods was 1.73% (95% CI, 0.5% -3.33%) with P value of 0.144 which is insignificant. Our results showed a strong agreement with other investigators as Garcia M et al [4], who found that FINE was successful to generate the nine planes in 98% -100% of cases and also Veronese P et al [10] who found that FINE was successful to generate the nine planes in 96% -100% of cases.…”
Section: Discussionsupporting
confidence: 93%
“…Such training occurred in a 2-day period and included: 1) attending didactic lectures on FINE; and 2) review of 16 previously acquired STIC volume datasets of normal fetal hearts using the FINE method. Specifically, the following features of FINE were reviewed during the training period (Table 1): 55,76,77,79 1) intelligent navigation technology; 2) STICLoop ™ and STICLoop criteria; 3) Anatomic Box® (learning how to identify and mark anatomical structures of the fetal heart); 4) diagnostic planes; 5) automatic labeling and its features; 6) Virtual Intelligent Sonographer Assistance (VIS-Assistance®) and its advantages in providing additional information, as well as how to perform double and triple VIS-Assistance; 80 and 7) intelligent and marking alerts. Moreover, the same investigator was provided a written manual on FINE and underwent a practical session on how to technically use the system (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…43,55 However, the use of software to perform manual navigation 76 through such volume datasets is time consuming, highly operator dependent, and requires a thorough knowledge of cardiac anatomy. 7779 As a result, this process is difficult and impractical, especially when the fetal heart is abnormal. 80 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optimum interrogation of STIC volume data sets remains difficult . Recently, some studies have reported that fetal intelligent navigation echocardiography (FINE) is a novel and useful technology for automatically obtaining 9 recommended fetal cardiac views through the application of intelligent navigation technology in STIC volume data sets . The FINE method can simplify fetal cardiac examinations and reduce operator dependency.…”
mentioning
confidence: 99%